Estimation of energy expenditure and daily activity index on 185 subjects by a new personal computer system - Nishihara, T; Katsuki, F; Hori, M; Kagawa, C; Okuda, S; Utsu, T; Yoneda, I; Nasu, M; Yoneda, K (Eiyōgaku zasshi, 1988)
The procedure for estimating human energy expenditure and daily activity index by the “diary method” is both troublesome and time consuming. In an attempt to overcome such disadvantages, we devised a software for estimating them and developed a convenient use based on the menu. Appropriate types of activities from the graphically displayed list are selected. The major activities were input in terms of a multiple of 5, 10, 30 and 60 minutes. The minor activities which occur during the major ones are input in terms of minutes. Since the input was based on the graphically displayed timetable, it was possible for an operator well versed in this system to roughly estimate the total energy expenditure even during an interview with a respondent. The time required for estimation for one subject was between 10 and 20 minutes. The investigation was carried out on the activities of 185 subjects with several different occupations including housewives and students during two working days and one holiday. The mean value of daily activity index (x) of males engaged in works mostly in standing position was about 0.5 with variations according to the type of their activities on the working days. On the holiday, however, they tended to spend time in sleeping and sitting down for rest. The value x for sedentary male workers was about 0.4. The intensity of their activities was similar on the working days but not on the holiday. With housewives, the value x was about 0.6. Housewives who had jobs had a significantly lower x on the working days than those without jobs. But this difference was not observed on the holiday. One of the reasons for higher x of housewives with jobs is because RMR (relative metabolic rate) values for household works used for the analyses were determined 20 or 30 years ago and therefore they may not accurately represent the energy spent in recent household jobs. The subjects with lower x values tended to complain of breathlessness when they ran or climbed the stairs.